Effect of Gadolinium Orthovanadate Nanoparticles on Male Rabbits' Reproductive Performance under Oxidative Stress - Koshevoy, Vsevolod; Кошевой, Всеволод Ігоревич; Naumenko, Svitlana; Науменко, Світлана Валеріївна; Sklyarov, Pavlo; Sklyarov, Pavel; Sklyarov, P. M.; Skliarov, P. M.; Sklyarov, P.; Skliarov, Pavlo; Скляров, Павло Миколайович; Syniahovska, Kateryna; et al. (My University, 2022)
Oxidative stress as a leading factor of male infertility requires correction with modern pharmacological agents, particularly redox-active nanoparticles, to improve sperm quality and hormonal balance. The current experimental study aimed to investigate the effect of orthovanadate nanoparticles of rare earth elements, particularly Gadolinium, with pronounced redox properties on the reproductive function of male rabbits under oxidative stress. A total of 36 mature male Hyla rabbits were divided into three groups of intact control (n = 12) and two experimental groups, including rabbits ubder oxidative stress (n = 12), induced by the introduction of tert-Butyl hydroperoxide, and those under oxidative stress plus hydrosol of gadolinium orthovanadate nanoparticles (NPs, n = 12) intake for 14 days. There were four rabbits per three replicates in each group. Animals of all groups were kept on the same diet and had free access to water. The use of NPs led to an improvement in sperm quality indicators. There was an improvement in motility and ejaculate volume indicators (by 14.6% and 39.2%, respectively), a reduction of the content of morphologically abnormal sperm by 26.7%; normalization of sex hormones, an increase in the level of total testosterone (by 113%) with a decrease in 17-β-estradiol (by 16.5%). This sex hormones improvement led to an increase in the androgen saturation of the rabbit’s body (free androgen index at the end of the experiment was 36.5%). The obtained changes were accompanied by a decrease in the oxidative load, as evidenced by a reduced content of diene conjugates and thio-barbituric acid-reactive compounds in the blood serum of rabbits by 30.4% and 26.8%, compared to the control. At the same time, there was an increase in the antioxidant potential, especially its glutathione link – the activity of glutathione peroxidase and glutathione reductase (by 42.5% and 34.2%, respectively), and the content of reduced glutathione increased by 62.3%, compared to the indicators before the introduction of NPs. The results of the study confirmed the effectiveness of using gadolinium orthovanadate NPs to correct the reproductive function of males under oxidative stress. Оксидативний стрес як провідний фактор неплідності самців потребує корекції сучасними фармакологічними засобами, зокрема редокс-активними наночастинками, для покращення якості сперми та гормонального балансу. Сучасне експериментальне дослідження мало на меті дослідити вплив наночастинок ортованадату рідкоземельних елементів, зокрема гадолінію, з вираженими окислювально-відновними властивостями на репродуктивну функцію самців кролів за оксидативного стресу. Всього 36 статевозрілих самців кроликів породи Hyla розділили на три групи: інтактну контрольну (n = 12) і дві експериментальні групи, включаючи кроликів під окисним стресом (n = 12), індукованим введенням трет-бутилгідропероксиду, і кроликів під окисним стресом плюс гідрозоль наночастинок гадоліній ортованадату (НЧ, n = 12) протягом 14 днів. У кожній групі було по чотири кролики на три повтори. Тварини всіх груп утримувалися на однаковому раціоні та мали вільний доступ до води. Застосування НЧ призвело до покращення показників якості сперми. Відмічено покращення показників моторики та об’єму еякуляту (на 14,6% та 39,2% відповідно), зменшення вмісту морфологічно аномальних сперматозоїдів на 26,7%; нормалізація статевих гормонів, підвищення рівня загального тестостерону (на 113%) при зниженні 17-β-естрадіолу (на 16,5%). Таке покращення статевих гормонів призвело до підвищення андрогенної насиченості організму кролика (індекс вільного андрогену наприкінці експерименту становив 36,5%). Отримані зміни супроводжувалися зниженням окисного навантаження, про що свідчить зниження вмісту дієнових кон’югатів і тіобарбітурової кислоти в сироватці крові кролів на 30,4 % і 26,8 % порівняно з контролем. При цьому відмічено підвищення антиоксидантного потенціалу, особливо його глутатіонової ланки – активності глутатіонпероксидази та глутатіонредуктази (на 42,5% та 34,2% відповідно), а вміст відновленого глутатіону збільшився на 62,3% порівняно з до показників до введення НЧ. Результати дослідження підтвердили ефективність використання НЧ гадоліній ортованадату для корекції репродуктивної функції самців в умовах оксидативного стресу.
Вплив наночастинок ортованадату гадолінію на репродуктивну функцію самців кроликів при окислювальному стресі
Скляров Павло Миколайович https://orcid.org/0000-0002-4379-9583
Keywords: Reproductive performances; репродуктивні характеристики; Gadolinium orthovanadate; Гадолінію ортованадат; Male rabbits; самці кроликів; Nanoparticles; наночастинки; Oxidative stress; окислювальний стрес